2015
DOI: 10.1111/jsap.12337
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of the lentiform nuclei in dogs with portosystemic shunts

Abstract: This method of quantifying the T1-weighted magnetic resonance imaging signal intensity of the lentiform nuclei was reliable and showed that dogs with portosystemic shunts tend to have increased signal intensity. Further prospective studies are necessary to investigate the clinical significance and applications of these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 35 publications
0
10
1
Order By: Relevance
“…From the neurological point of view, affected dogs tend to show prosencephalic signs with altered mental status, circling, seizures, altered behaviour in association with mild ataxia, which are completely different signs compared with our case 19. Moreover, it is reported that in dogs with PSS on T1-weighted images on MRI, there is a hyperintensity of the lentiform nucleus that was not observed in this case 20. A clear relationship between postprandial bile acids elevation and CGD has not been found.…”
Section: Discussioncontrasting
confidence: 60%
“…From the neurological point of view, affected dogs tend to show prosencephalic signs with altered mental status, circling, seizures, altered behaviour in association with mild ataxia, which are completely different signs compared with our case 19. Moreover, it is reported that in dogs with PSS on T1-weighted images on MRI, there is a hyperintensity of the lentiform nucleus that was not observed in this case 20. A clear relationship between postprandial bile acids elevation and CGD has not been found.…”
Section: Discussioncontrasting
confidence: 60%
“…14 HE is commonly observed in man secondary to a variety of liver diseases, but the pathogenesis remains unclear. HE may cause chronic alterations in the central nervous system (CNS), [15][16][17][18][19][20] and there is direct evidence of astrocyte alterations in the brains of dogs with CPSS. 10,21 The CNS is believed to adapt to an abnormal metabolic environment preoperatively, and the sudden change caused by surgical attenuation favors an excitatory state.…”
Section: Introductionmentioning
confidence: 99%
“…A PSS is an abnormal communication between the portal vascular system and the systemic circulation 1–4. Higher concentrations of endogenous and exogenous toxins that are normally metabolised or eliminated bypass the liver 1–3. Since metabolism or detoxification is not performed first pass by the liver, there is impaired clearance of ammonia and other toxins there and HE occurs 3.…”
Section: Discussionmentioning
confidence: 99%
“…HE is a progressive disorder with a wide spectrum of neuropsychiatric abnormalities and motor disturbances 4 5. The clinical signs associated with PSS result from HE involving a variety of neurological signs, including behavioural changes, ataxia, unresponsiveness, pacing, circling, blindness, seizures and coma2 4 and death 6…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation